The effect of early trough level of infliximab on subsequent disease course in patients with Crohn disease: A prospective cohort study. Issue 29 (17th July 2020) - Ishida, Natsuki; Miyazu, Takahiro; Sugiyama, Tomohiro; Tamura, Satoshi; Kagami, Takuma; Tani, Shinya; Yamade, Mihoko; Iwaizumi, Moriya; Hamaya, Yasushi; Osawa, Satoshi; Furuta, Takahisa; Sugimoto, Ken
Abstract : Abstract: Decreased trough level of infliximab (TLI) is associated with diminished efficacy in patients with Crohn disease (CD). We examined whether TLI at 14 weeks subsequent to the start of infliximab (IFX) treatment would impact long-term clinical course. Serum IFX levels and antibodies to IFX (ATI) at 14 and 54 weeks after IFX administration were measured in 12 patients with mild to moderate CD. We examined patient background, clinical severity, blood test values, and the relationship between ATI and TLI up to 108 weeks. We compared the group with TLI < 3 μg/mL at 14 weeks (TLI(14) < 3 group) the group with TLI > 3 μg/mL (TLI(14) ≥ 3 group). Patients in the TLI(14) ≥ 3 group were significantly more likely to use immunomodulators before IFX treatment induction ( P  = .01). At 54 weeks, 2 cases of ATI production were observed in the TLI(14) < 3 group, but no ATI production was observed in the TLI(14) ≥ 3 group. TLI in the TLI(14) ≥ 3 group at 54 weeks was significantly higher than in the TLI(14) < 3 group (6.5 μg/mL vs 1.0 μg/mL; P  < .01). Although CD activity index and serum albumin values in the TLI(14) ≥ 3 group at 14, 54, and 108 weeks significantly improved compared to baseline, these improvements were not observed in the TLI(14) < 3 group. The remission maintenance rate at 108 weeks evaluated with the Kaplan–Meier method was significantly higher in the TLI(14) ≥ 3 group than the TLI(14) < 3 group (100% vs 33.3%; P  = .02). The TLI 14 weeks after IFX treatment in patients with CD affects long-term outcome.